Water-enhanced CO2 capture in metal–organic frameworks - Cammarere, Celine; Cortés, Jaeden; Glover, T. Grant; Snurr, Randall Q.; Hupp, Joseph T.; Liu, Jian (Frontiers in Chemistry, 2025)
CO2 capture from post-combustion flue gas originating from coal or natural gas power plants, or even from the ambient atmosphere, is a promising strategy to reduce the atmospheric CO2 concentration and achieve global decarbonization goals. However, the co-existence of water vapor in these sources presents a significant challenge, as water often competes with CO2 for adsorption sites, thereby diminishing the performance of adsorbent materials. Selectively capturing CO2 in the presence of moisture is a key goal, as there is a growing demand for materials capable of selectively adsorbing CO2 under humid conditions. Among these, metal–organic frameworks (MOFs), a class of porous, highly tunable materials, have attracted extensive interest for gas capture, storage, and separation applications. The numerous combinations of secondary building units and organic linkers offer abundant opportunities for designing systems with enhanced CO2 selectivity. Interestingly, some recent studies have demonstrated that interactions between water and CO2 within the confined pore space of MOFs can enhance CO2 uptake, flipping the traditionally detrimental role of moisture into a beneficial one. These findings introduce a new paradigm: water-enhanced CO2 capture in MOFs. In this review, we summarize these recent discoveries, highlighting examples of MOFs that exhibit enhanced CO2 adsorption under humid conditions compared to dry conditions. We discuss the underlying mechanisms, design strategies, and structural features that enable this behavior. Finally, we offer a brief perspective on future directions for MOF development in the context of water-enhanced CO2 capture.